What are Optimal Bacteriological Screening Test Cut-Offs for Pasteurized Donor Human Milk Intended for Feeding Preterm Infants?. (February 2021) - Clifford, Vanessa; Klein, Laura D.; Sulfaro, Christine; Karalis, Tass; Hoad, Veronica; Gosbell, Iain; Pink, Joanne
Background: Definitive criteria for microbial screening of pasteurized donor human milk are not well established and international recommendations vary. Aims: (1) To review pasteurized donor human milk batch discard due to failed microbial screening criteria at our milk bank (following United Kingdom National Institute of Clinical Excellence guidelines), and (2) to compare our known milk discard proportion with estimated milk discard proportions that would be required by other international milk bank guidelines. Methods: We reviewed our microbial screening results ( N = 783) over 18-months (July 2018-December 2019) and compared our known milk discard proportion with estimated milk discard proportions using other international milk bank guidelines. Results: Of samples, n = 50 (6.4%) failed pre-pasteurization screening, most commonly due to the presence of >10 4 CFU/mL Enterobacterales in the pre-pasteurization sample ( n = 30; 3.8%). Two (0.3%) samples failed post-pasteurization screening, with Bacillus cereus identified in both cases, resulting in total discard proportion of 6.7% ( n = 52) of batches. Applying European Milk Bank Association recommended bacterial screening criteria, approximately 23.3% ( n = 183) of milk batches would have been discarded. Conclusions: Further research is required to justify the stringent European Milk Bank Association recommendations for pre-pasteurization discard criteria, although we believe that a post-pasteurization acceptance criterion of <1 CFU/mL is appropriate and aligns with international guidance. Further work is needed to understand pasteurized donor human milk microbiological safety risks, to better integrate screening criteria within current food standards regulation, and to consider risk-based assessment including the impact on availability and affordability.